Dehydration of egg yolks by spray drying at different temperatures - Magnani Grassi, Thiago Luis [UNESP] (2015)
The objective of this work was to evaluate the effect of dehydration temperatures by spray drying on the microbiological, physical, and chemical characteristics of egg powder and on the yield of the process. Dehydration was performed by spray drying at 90, 120, and 150 degrees C, with five replicates for each treatment. The yield was estimated by the ratio between the amount of egg yolk powder obtained and the amount of in natura egg yolk used in the drying process. The dehydrated egg yolks were analyzed for chemical composition, objective color, and rancidity. For microbiological analyzes, the presence of coagulase-positive staphylococcus, by direct plate count; Salmonella spp., within a 25-g sample; and coliforms, at 45 degrees C, was detected. The spray drying temperature influenced the moisture content of yolk powder, without affecting the levels of proteins, lipids and ash, the microbiological characteristics, or the rancidity of the final products. Higher drying temperatures produce higher product yield, but, at 150 degrees C, there is a darkening and a reduction in the intensity of the yellow color of yolk powder.